2023
DOI: 10.14814/phy2.15609
|View full text |Cite
|
Sign up to set email alerts
|

Food readjustment plus exercise training improves cardiovascular autonomic control and baroreflex sensitivity in high‐fat diet‐fed ovariectomized mice

Abstract: Despite consensus on the benefits of food readjustment and/or moderate‐intensity continuous exercise in the treatment of cardiometabolic risk factors, there is little evidence of the association between these two cardiovascular risk management strategies after menopause. Thus, the objective of this study was to evaluate the effects of food readjustment and/or exercise training on metabolic, hemodynamic, autonomic, and inflammatory parameters in a model of loss of ovarian function with diet‐induced obesity. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Twenty-four hours after surgery, hemodynamic measurements were obtained, and the animals were awake and allowed to move freely in their cages. The cannula was coupled to a biological signal transducer for recording blood pressure signals (Blood Pressure XDCR, Kent Scientific, Litchfield, CT, USA) for 30 min using a digital converter (Windaq DI720, 4-kHz sampling frequency, Dataq Instruments) The recorded data were analyzed on a beat-to-beat basis to quantify changes in mean arterial pressure (MAP) and HR 24 , 25 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four hours after surgery, hemodynamic measurements were obtained, and the animals were awake and allowed to move freely in their cages. The cannula was coupled to a biological signal transducer for recording blood pressure signals (Blood Pressure XDCR, Kent Scientific, Litchfield, CT, USA) for 30 min using a digital converter (Windaq DI720, 4-kHz sampling frequency, Dataq Instruments) The recorded data were analyzed on a beat-to-beat basis to quantify changes in mean arterial pressure (MAP) and HR 24 , 25 .…”
Section: Methodsmentioning
confidence: 99%
“…For frequency domain analysis of cardiovascular autonomic modulation, PI and SAP were divided into segments and overlapped by 50%, cubic spline-decimated to be equally spaced in time after linear trend removal; power spectral density was obtained through the fast Fourier transformation. The components of spectral analysis were quantified in the very low-frequency ranges (VLF-PI, 0–0.4 Hz), low-frequency ranges (LF-PI, 0.4–1.5 Hz), and high-frequency ranges (HF-PI, 1.5–5.0 Hz) 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, experimental studies have demonstrated that rats subjected to ovarian hormone deprivation due to OVX surgery present with increased blood pressure (BP), sympathetic tonus, oxidative stress, and body weight, and reduced baroreceptor reflex sensitivity (BRS) compared to control female rats. On the other hand, these studies showed that the exercise training (ET) recommended after OVX improved the cardiometabolic dysfunction [6,7].…”
Section: Introductionmentioning
confidence: 99%